Analysis of the Implementation of Health Development Planning Policy in Satui Sub-District, Tanah Bumbu Regency - Selveana Wati; Anhar Yani; Akhmad Abdurahman; Nuril Mawaddah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This study aims to analyze the implementation of the Musyawarah Perencanaan Pembangunan (Musrenbang) policy in the health sector in Satui Subdistrict, Tanah Bumbu Regency, and to identify the challenges encountered during its implementation. Musrenbang serves as a participatory planning forum mandated by the national development planning system to accommodate community aspirations in regional development. This research employed a qualitative descriptive approach, using observation, interviews, and documentation involving subdistrict officials, village heads, local legislators, health office representatives, and community members. Data were analyzed using Grindle’s policy implementation model, which emphasizes the dimensions of policy content and implementation context. The findings indicate that procedurally the Musrenbang process has been conducted in accordance with established mechanisms, particularly in collecting and prioritizing community proposals. However, implementation remains suboptimal due to budget constraints, policy intervention, and limited public participation. Strengthening stakeholder commitment and enhancing community engagement are essential to improve the effectiveness of participatory health development planning.